ASSESSMENT OF MEDICATION ADHERENCE AMONG OUTPATIENTS WITH PEPTIC ULCER DISEASE AT MILITARY HOSPITAL 103 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of medication adherence and to analyze several factors associated with compliance outcomes among outpatients with peptic ulcer disease (PUD) at Military Hospital 103. Subjects and Methods: A cross-sectional descriptive study with analytical components was conducted on 184 outpatients diagnosed with PUD confirmed by endoscopy at Military Hospital 103 from 01/2025 to 12/2025. Medication adherence status was evaluated using the 8-item Morisky Medication Adherence Scale (MMAS-8), with adherence defined as a score of ≥ 6. Associated factors and their relationship with clinical symptom improvement were analyzed using binary logistic regression models to determine odds ratios (OR) with a 95% confidence interval (95%CI). Results: The medication adherence rate among the study participants was 86.4%, with a mean MMAS-8 score of 7.1 ± 0.78. Students demonstrated a significantly lower adherence rate compared with individuals engaged in freelance occupations (OR = 0.13; 95% CI: 0.03-0.59; p = 0.007). No statistically significant associations were observed between medication adherence and age, sex, educational level, place of residence, or caregiver status (p > 0.05). The proportion of patients with complete symptom resolution was higher in the adherence group than in the non-adherence group (53.46% vs. 20.0%). Adherent patients were 6.8 times more likely to achieve complete symptom resolution compared with non-adherent patients (OR = 6.80; 95% CI: 1.85-24.96; p = 0.003). Conclusion: The medication adherence rate among outpatients with peptic ulcer disease at Military Hospital 103 was 86.4%. Students had a lower adherence rate than those in freelance occupations. Medication adherence was associated with improvement in the clinical symptoms of the disease.
Keywords: Treatment adherence; Medication adherence; Peptic ulcer disease; MMAS-8; Outpatient care.